Blue Light Treatment but Not Green Light Treatment After Pre-exposure to UV-B Stabilizes Flavonoid Glycoside Changes and Corresponding Biological Effects in Three Different Brassicaceae Sprouts - Neugart, Susanne; Majer, Petra; Schreiner, Monika; Hideg, Éva (Frontiers in Plant Science, 2021)
Ultraviolet-B (UV-B; 280–315 nm) radiation induces the biosynthesis of secondary plant metabolites such as flavonoids. Flavonoids could also be enhanced by blue (420–490 nm) or green (490–585 nm) light. Flavonoids act as antioxidants and shielding components in the plant’s response to UV-B exposure. They are shown to quench singlet oxygen and to be reactive to hydroxyl radical. The aim was to determine whether treatment with blue or green light can alter flavonoid profiles after pre-exposure to UV-B and whether they cause corresponding biological effects in Brassicaceae sprouts. Based on their different flavonoid profiles, three vegetables from the Brassicaceae were selected. Sprouts were treated with five subsequent doses (equals 5 days) of moderate UV-B (0.23 kJ m–2 day–1 UV-BBE), which was followed with two subsequent (equals 2 days) doses of either blue (99 μmol m–2 s–1) or green (119 μmol m–2 s–1) light. In sprouts of kale, kohlrabi, and rocket salad, flavonoid glycosides were identified by HPLC-DAD-ESI-MSn. Both Brassica oleracea species, kale and kohlrabi, showed mainly acylated quercetin and kaempferol glycosides. In contrast, in rocket salad, the main flavonol glycosides were quercetin glycosides. Blue light treatment after the UV-B treatment showed that quercetin and kaempferol glycosides were increased in the B. oleracea species kale and kohlrabi while—contrary to this—in rocket salad, there were only quercetin glycosides increased. Blue light treatment in general stabilized the enhanced concentrations of flavonoid glycosides while green treatment did not have this effect. Blue light treatment following the UV-B exposure resulted in a trend of increased singlet oxygen scavenging for kale and rocket. The hydroxyl radical scavenging capacity was independent from the light quality except for kale where an exposure with UV-B followed by a blue light treatment led to a higher hydroxyl radical scavenging capacity. These results underline the importance of different light qualities for the biosynthesis of reactive oxygen species that intercept secondary plant metabolites, but also show a pronounced species-dependent reaction, which is of special interest for growers.